2022
DOI: 10.3390/ijms23020685
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Formation of Cyclodextrin-Based Pseudopolyrotaxanes of Polyethylene Glycol: Kinetic and Structural Aspects

Abstract: Pseudopolyrotaxanes (PPRs) are supramolecular structures consisting of macrocycles able to thread on a linear polymer chain in a reversible, non-covalent way, often referred to in the literature as “molecular necklaces”. While the synthesis and reaction mechanisms of these structures in solution have been widely described, their solvent-free production has received little attention, despite the advantages that this route may offer. We propose in this work a kinetic mechanism that describes the PPR formation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We observed that both the HP-α-CD and HP-β-CD present two peaks in the 2 θ ranges of 10–15° and 15–25°, which could be related to their cage-like structure. 45 It should be noted that these peaks are broad evidencing the amorphous characters of the investigated cyclodextrins. 46 In addition, the diffractograms of both cyclodextrins evidenced a wide band centred at ca.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…We observed that both the HP-α-CD and HP-β-CD present two peaks in the 2 θ ranges of 10–15° and 15–25°, which could be related to their cage-like structure. 45 It should be noted that these peaks are broad evidencing the amorphous characters of the investigated cyclodextrins. 46 In addition, the diffractograms of both cyclodextrins evidenced a wide band centred at ca.…”
Section: Resultsmentioning
confidence: 88%
“…Similar observations are reported for the inclusion of PEG400 in the cavity of a-CD. 45 Moreover, the intensity of the peak characteristic of the copolymer was reduced. The latter can be attributed to the formation of the inclusion complexes.…”
Section: Structural Properties Of L35/cd Polypseudorotaxanesmentioning
confidence: 99%